Pancreatectomy in Multiple Endocrine Neoplasia Type 1-Related Gastrinomas and Pancreatic Endocrine Neoplasias - Francesco Tonelli; Geri Fratini; Gabriella Nesi; Maria Silvia Tommasi; Giacomo Batignani; Alberto Falchetti; Maria Luisa Brandi (2006)
The aim of this study was to evaluate the results of pancreatic resection in pancreatic endocrine neoplasias (PENs) in patients affected by multiple endocrine neoplasia type 1 (MEN1) syndrome.Since these tumors often show an indolent course, the role of diagnostic procedures and type of surgical approach are controversial. Experience with new diagnostic approaches and more aggressive surgery is still limited.Sixteen MEN1 patients were referred to our Surgical Unit (1992-2003) and were operated on for the indications of hypergastrinism, hypoglycemia, and/or pancreatic endocrine neoplasias larger than 1 cm. Zollinger-Ellison syndrome (ZES) was present in 13 patients, 2 of whom experienced a recurrence after previous surgery. Preoperative tumor localization was carried out using ultrasonography (US), computed tomography (CT), endoscopic ultrasonography (EUS), somatostatin receptor scintigraphy (SSRS), or selective arterial secretin injection (SASI). Rapid intraoperative gastrin measurement (IGM) was carried out in 8 patients, and 1 patient also underwent an intraoperative secretin provocative test.Either pancreatoduodenectomy (PD) or total pancreatectomy (TP) or distal pancreatectomy was performed. There was no postoperative mortality; 37% complications included pancreatic (27%) and biliary (6%) fistulas, abdominal collection (6%), and acute pancreatitis (6%). EUS and SSRS were the most sensitive preoperative imaging techniques. At follow-up, 10 of 13 hypergastrinemic patients (77%) are currently eugastrinemic with negative secretin provocative test, while 3 are showing a recurrence of the disease. All patients affected by insulinoma were cured.MEN1 tumors should be considered surgically curable diseases. IGM may be of value in the assessment of surgical cure. Our experience suggests that PD is superior to less radical surgical approaches in providing cure with limited morbidity in MEN1 gastrinomas and pancreatic neoplasias.